Investigating impact of health belief and trust on technology acceptance in smartwatch usage: Turkish senior adults case - Gündüz, Nalan; Zaim, Selim; Erzurumlu, Yaman Ömer (Emerald Publishing, 2024)
Purpose: This paper aims to investigate the influence of health beliefs and trust by senior adults as associated with the perceived ease of use and perceived usefulness, for the acceptance of smart technology with a focus on smartwatch technology. Design/methodology/approach: Structural equation modeling is used to conceptualize the model using survey data collected from 243 randomly selected senior adults 60+ years of age. Findings: This paper presents that perceived usefulness, perceived ease of use, trust and health belief are direct and indirect predictors of senior adults’ technology acceptance and intention to use smartwatch technology. Research limitations/implications: The study reveals the moderator effect of social influence on relation between perceived usefulness, perceived ease of use and intention to use. The authors highlight the effect of health belief and trust on perceived usefulness and perceived ease of use and the role of intention to use smartwatch technology. Practical implications: The authors contribute bridging developers of health technologists and senior adults as end-user perspectives. For marketing of health-care technology products, specifically smartwatch, to seniors, a focus on health beliefs and trust is essential to build, maintain and improve perceived usefulness and perceived ease of use. Originality/value: The present study contributes empirical evidence to the literature on factors affecting the acceptance of the smartwatch technology by senior adults.
Keywords: Health belief; Senior adults; Senior technology acceptance model; Smartwatch; Social influence; Trust